PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN STUDI PADA PELANGGAN PERUSAHAAN ZYX DI KOTA SERANG - Tabroni, Tabroni (Yayasan Education and Social Center, 2024)
This research aims to explore the influence of price and product quality on consumer purchasing decisions. By focusing on price variables, product quality, and purchasing decisions, this research provides insight into market dynamics in an increasingly complex competitive environment. Data was collected through a survey of 144 registered customers of the ZYX Company in Serang City, using a Likert scale-based questionnaire. The analysis results show that price has a positive and significant influence on purchasing decisions. Competitive prices and attractive discounts have been proven to increase consumer motivation to buy products or use company services. On the other hand, product quality does not show a significant influence on purchasing decisions. This shows that although product quality is improving, this factor does not directly motivate consumers to buy, especially in markets with high price sensitivity. This research provides practical implications for company managers to pay more attention to price strategy as the main element in attracting consumer attention. Additionally, an optimal combination of price, service quality and product quality can be the key to driving customer loyalty. This study recommends further research to understand the mediating influence of competitiveness and profitability in purchasing decisions to improve business sustainability.